Cases on applied and therapeutic humor - Kelly, Stephanie, 1984-; Cundall, Michael K., 1974- (Advances in medical diagnosis, treatment, and care (AMDTC) book series., 2021)
"This book examines on applied and therapeutic humor. It covers topics ranging from propriety, effectiveness, perception, and cultural variables"--